Oxygen-deficient ammonium vanadate for flexible aqueous zinc batteries with high energy density and rate capability at −30 °C. (March 2021) - He, Tao; Ye, Yusheng; Li, Hui; Weng, Suting; Zhang, Qinhua; Li, Matthew; Liu, Tongchao; Cheng, Jianli; Wang, Xuefeng; Lu, Jun; Wang, Bin
Graphical abstract: Abstract: Aqueous zinc batteries (AZBs) have received significant attention owing to environmental friendliness, high energy density and inherent safety. However, lack of high-performance cathodes has become the main bottleneck of AZBs development. Here, oxygen-deficient NH4 V4 O10− x · n H2 O (NVOH) microspheres are synthesized and used as cathodes for AZBs. The experimental test and theoretical calculations demonstrate that the oxygen vacancies in the lattice lower the Zn 2+ diffusion energy barrier, which enables fast Zn 2+ diffusion and good electrochemical performance in a wide temperature range. The suppressed side reactions also can help to improve the low temperature performance. NVOH shows a high energy density of 372.4 Wh kg −1 and 296 Wh kg −1 at room temperature and −30 °C, respectively. Moreover, NVOH maintains a 100% capacity retention after 100 cycles at 0.1 A g −1 and ∼94% capacity retention after 2600 cycles at 2 A g −1 and −30 °C. Investigation into the mechanism of the process reveals that the capacity contribution of surface capacitive behaviors is dominant and capacity attenuation is mainly caused by the decay of diffusion-controlled capacity. Furthermore, flexible AZBs can steadily power portable electronics under different bending states, demonstrating its great potential in wide-temperature wearable device.